Influence of Fractional Differential on Correlation Coefficient between EC1:5 and Reflectance Spectra of Saline Soil - Nan Xia; Tashpolat Tiyip; Ardak Kelimu; Ilyas Nurmemet; Jianli Ding; Fei Zhang; Dong Zhang (Journal of Spectroscopy)
Soil salinization is one of the most serious environmental issues in arid and semiarid area with severe social, economic, and ecological problems. At present, most inversion models are based on raw reflectance spectra or integer differential transform. In this study, we measured the hyperspectral reflectance and EC1:5 of soil samples collected form Ebinur Lake to analyze the influence of fractional differential on correlation coefficient between EC1:5 and reflectance spectra. The results showed that the fractional differential increased sensibly the accuracy for the analysis of the reflectance spectra. The study might provide a new insight for monitoring soil salinity using hyperspectral data, and further researches should be concentrated on physical meaning of fractional differential in hyperspectral data to provide theoretical basis to building, describing, and spreading inversion models.